TEACHERS’ PERCEPTION ABOUT TOTAL PHYSICAL RESPONSE METHOD IN TEACHINNG SPEAKING SKILL AT SD ISLAM AL-FALAH JAMBI - Selvi Azli; Yanto Yanto; Nely Arif (Universitas Jambi, 2016)
The purposes of this qualitative study were to find out the voices of teachers about total physical response method in teaching speaking skill and describe activities that teachers usually give in teaching speaking skill using total physical response method. Data for this study were collected through a demographic background, interview, and observation. The demographic data were analyzed descriptively. The interviews data were analyzed using thematic analysis. The observation were analyzed descriptively using observation sheet and using video recorded for recorded the process of teaching speaking skill using total physical response method in the classroom. There were five English teachers as participants in interview and there were two English teachers as participants in observation. Based on the research results, there were five major themes emerged from the data related to the voices of teachers about TPR method in teaching speaking skill such as body gesture in teaching speaking skill, difficulties in learning vocabulary, effective method in teaching speaking skill, participation and interaction in teaching speaking skill, and role play in teaching speaking skill. As the suggestion, TPR method is recommended to be applied in teaching speaking and teachers who apply this method were suggested to develop appropriate classroom management.